After International Law: Anthropology Beyond the "Age of Human Rights". (16th August 2021) - Goodale, Mark
Abstract : This essay examines the ways in which anthropologists have tracked the rise and fall of international law after the end of the Cold War. It argues that anthropological research has made important contributions to the wider understanding of international law as a mechanism for social and political change, a framework for protecting vulnerable populations, and a language through which collective identities can be expressed and valorized. Yet, over time, international law has lost many of these expansive functions, a shift that anthropologists have also studied, although with greater reluctance and difficulty. The essay explains the ways in which particular categories of international law, such as human rights and international criminal justice, grew dramatically in importance and power during the 1990s and early 2000s, a shift whose complexities anthropologists studied at the local level. As the essay also explains, anthropological research began to detect a weakening in human rights implementation and respect for international legal norms, a countervailing shift that has broader implications for the possibilities for international cooperation and the resolution of conflicts, among others. At the same time, the retreat of international law from its highpoint in the early post-Cold War years has given way to the reemergence of non-legal strategies for advancing change and accounting for past injustices, including strategies based on social confrontation, moral shaming, and even violence.